Ketergantungan Negara terhadap Pasar Internasional dalam Mencapai Ketahanan Pangan (Dengan fokus perbandingan negara Indonesia dengan Vietnam, Malaysia, dan Amerika Serikat) - Ni Made Laksmi Udayani; Andi Akhmad Basith Dir; Hermini Susiatiningsih (Jurnal Ilmiah Hubungan Internasional, 2020)
Food security become very important as food crisis occurred in 2008. Under the administration of Susilo Bambang Yudhoyono in 2009 to 2014, the crisis due to increase in population in Indonesia encourages increase in food demand. However, to fulfill Indonesia’s food demand it still depends on the availability from international market. This research aims to analyze why countries like Indonesia dependent on international markets for food security aspect despite having the capability to achieve fulfillment on food. To analyze the reasons, the concepts of comparative advantage, dependency, and national capabilities will be use to analyze the factors on why nations depend on international market to achieve its food security. Accompanied by a comparison between Indonesia with Vietnam, Malaysia, and United States to see the similarities and differences to achieved food security in the international market. With qualitative research methods and comparison focus on explanative research also using literature studies in data collection. The results of this study finds that Indonesia dependence are influenced by comparative advantage policy of other countries which in this case are Vietnam and Malaysia, the international market system that encourages dependency, and Indonesia inability to maximizing its national capability compared to United States. Keywords: dependency, comparative advantage, national capabilities, Indonesia, food security.